Association Between Helicobacter pylori Infection and Otitis Media With Effusion Risk in Children: A Systematic Review and Meta‐analysis. (2nd June 2020) - Wu, Xiaohui; Zheng, Yun; Gao, Xingqiang; Li, Gang; Cao, Qiuxue
Abstract : Objective: To investigate the potential correlation between Helicobacter pylori infection and otitis media with effusion (OME) risk in children. Data Sources: Electronic databases were searched, including Cochrane Library, PubMed, Embase, China Biology Medicine disc, China Science and Technology Journal Database, Wanfang Database, and China National Knowledge Infrastructure Database. Review Methods: A systematic review and meta‐analysis were conducted with Revman 5.3 software. Combined odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate infection‐disease association. Results: In total, 11 studies from 9 articles regarding H pylori infection and OME risk were enrolled in this meta‐analysis. A significant association between H pylori infection and OME was detected for both adenoid samples from the case group (OR, 2.75; 95% CI, 1.43‐5.30; P =. 002) and middle ear fluid samples from the case group (OR, 4.45; 95% CI, 2.52‐7.88; P <. 00001). Subgroup analyses suggested a stronger correlation in African and Asian populations. Conclusion: This study indicated the correlation between H pylori infection and increased risk of OME in children, especially in African and Asian populations. Further well‐designed studies regarding the white population are strongly recommended in the future.